RETRACTED: Do Surrounding People's Emotions Affect Judgment of the Central Person's Emotion? Comparing Within Cultural Variation in Holistic Patterns of Emotion Perception in the Multicultural Canadian Society - Masuda, Takahiko; Shi, Shuwei; Varma, Pragya; Fisher, Delaney; Shirazi, Safi (Frontiers in Human Neuroscience, 2022)
Previous studies in cultural psychology have suggested that when assessing a target person's emotion, East Asians are more likely to incorporate the background figure's emotion into the judgment of the target's emotion compared to North Americans. The objective of this study was to further examine cultural variation in emotion perception within a culturally diverse population that is representative of Canada's multicultural society. We aimed to see whether East-Asian Canadians tended to keep holistic tendencies of their heritage culture regarding emotion perception. Participants were presented with 60 cartoon images consisting of a central figure and four surrounding figures and were then asked to rate the central figure's emotion; out of the four cartoon figures, two were female and two were male. Each character was prepared with 5 different emotional settings with corresponding facial expressions including: extremely sad, moderately sad, neutral, moderately happy, and extremely happy. Each central figure was surrounded by a group of 4 background figures. As a group, the background figures either displayed a sad, happy, or neutral expression. The participant's task was to judge the intensity of the central figures' happiness or sadness on a 10-point Likert scale ranging from 0 (not at all) to 9 (extremely). For analysis, we divided the participants into three groups: European Canadians (N = 105), East Asian Canadians' (N = 104) and Non-East Asian/Non-European Canadians (N = 161). The breakdown for the Non-East Asian/Non-European Canadian group is as follows: 94 South Asian Canadians, 25 Middle Eastern Canadians, 23 African Canadians, 9 Indigenous Canadians, and 10 Latin/Central/South American Canadians. Results comparing European Canadians and East Asian Canadians demonstrated cultural variation in emotion judgment, indicating that East Asian Canadians were in general more likely than their European Canadian counterparts to be affected by the background figures' emotion. The study highlights important cultural variations in holistic and analytic patterns of emotional attention in the ethnically diverse Canadian society. We discussed future studies which broaden the scope of research to incorporate a variety of diverse cultural backgrounds outside of the Western educational context to fully comprehend cultural variations in context related attentional patterns.